Do Smartphones Create a Coordination Problem for Face‐to‐Face Interaction? Leveraging Game Theory to Understand and Solve the Smartphone Dilemma. (4th March 2020) - Aktipis, Athena; Whitaker, Roger; Ayers, Jessica D.
Abstract: Smartphone use changes the landscape of social interactions, including introducing new social dilemmas to daily life. The challenge of putting down one's smartphone is an example of a classic coordination problem from game theory: the stag hunt game. In a stag hunt game, there are two possible coordination points, one that involves big payoffs for both partners (e.g., working together to hunt large game like stag) and one that involves smaller payoffs for both partners (e.g., individually hunting small game like rabbits) but is safer because it does not require that your partner choose that option as well. This is similar to the challenges of putting down smartphones to have a face‐to‐face interaction: you and your interaction partner might both prefer the higher payoff option of having a face‐to‐face interaction, but neither of you wants to put down your phone and risk not having anything to do in the meantime. It is also discussed how new technological innovations are changing the payoffs of face‐to‐face conversation versus side‐by‐side smartphone scrolling. Insights that come from applying game theory to this "social media dilemma" are discussed here and potential solutions that come out of a game theoretic analysis are offered. Also see the video abstract here https://youtu.be/9esL578zM‐E Abstract : We all face this dilemma: Put down the smartphone to have a face‐to‐face conversation or safely scroll your online feed? This is a modern manifestation of a classic game theoretic problem called the "stag hunt game." This problem and ways to solve it, including developing a new app that allows social contacts to opt‐in to a coordinated blackout is discussed.